SIZE OF METASTATIC INFILTRATION IN THE SENTINEL NODE AS A PREDICTOR OF NON‑SENTINEL NODES INVOLVEMENT - Andrade, Danúbia Ariana de; Carvalho, Filomena Marino; Aguiar, Fernando Nalesso; Jacomo, Alfredo Luiz; Barros, Alfredo Carlos Simões Dornellas de (Mastology, 2021)
Introduction: The broad acceptance of sentinel lymph node biopsy (SLNB) led to an analysis for finding out the anatomo- pathological characteristics that can help predict the involvement of other axillary lymph nodes (LN) in positive sentinel lymph node (SLN) cases. Currently, it is very appropriate to investigate the cases that enable the omission of complete axil- lary dissection (CAD), even considering the involvement of the SLN. Some important studies on this theme were published, e.g., ACOSOG Z0011, and AMAROS. However, their results were not accepted uniformly enough because of methodological inconsistencies. Objectives: We aimed at providing a complementary basis for a pragmatic analysis of CAD after a positive SLNB in breast cancer. Methods: This is a cross-sectional study. Clinical and anatomopathological data were collected in patients with early-infiltrating breast cancer that were treated with SLNB, followed by CAD. Statistical analyses were performed using binary logistic regression and multiple logistic regression. Results: Out of 129 patients evaluated, com- promise of non-sentinel additional lymph nodes was observed in 47 (36.4%) patients. According to an univariate analysis, the parameters related to non-SLN compromise were the tumor size in anatomopathological exam, histological grade III, the presence of peritumoral vascular embolism in focal area, compromise of more than one SLN, LN compromise rate of 100%, the presence of extracapsular neoplastic extension, perilymphnodal vascular involvement, perilymphatic fat compromise, and twenty or more dissected non-SNLs. The variables that increased the chance of compromise of non-SNL in the multivariate analysis were presented in following table with an accuracy of 81% (Figure). Conclusions: The tumor size on a clinical examination of the T2 category, the presence of two or more neoplastic foci in the SNL, and the size of the metastasis > 4.0 mm are the parameters that favor complete axillary lymphadenectomy.